2018
DOI: 10.1523/jneurosci.1122-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecan Directs Extracellular Matrix-Mediated Neuronal Plasticity

Abstract: In the adult brain, the extracellular matrix (ECM) influences recovery after injury, susceptibility to mental disorders, and is in general a strong regulator of neuronal plasticity. The proteoglycan aggrecan is a core component of the condensed ECM structures termed perineuronal nets (PNNs), and the specific role of PNNs on neural plasticity remains elusive. Here, we genetically targeted the Acan gene encoding for aggrecan using a novel animal model. This allowed for conditional and targeted loss of aggrecan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
166
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 37 publications
(28 reference statements)
11
166
2
Order By: Relevance
“…The somata and dendrites of most of these PV+ neurons are surrounded by perineuronal nets (PNNs), condensed extracellular matrix structures that surround synapses and are involved in the control of developmental and adult plasticity (5)(6)(7)(8). Digestion of inhibitory CSPGs (the main effectors of PNNs) with chondroitinase ABC (ChABC), enables increased formation of inhibitory synapses on PV + neurons (2,9), and enhances memory formation and duration in young animals, as does transgenic attenuation of PNNs (10,11). Moreover in animals with defective memory due to pathology from mutant tau or amyloid-beta, CSPG digestion or antibody treatment to block inhibitory 4-sulphated CS-GAGs restores memory to normal levels (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…The somata and dendrites of most of these PV+ neurons are surrounded by perineuronal nets (PNNs), condensed extracellular matrix structures that surround synapses and are involved in the control of developmental and adult plasticity (5)(6)(7)(8). Digestion of inhibitory CSPGs (the main effectors of PNNs) with chondroitinase ABC (ChABC), enables increased formation of inhibitory synapses on PV + neurons (2,9), and enhances memory formation and duration in young animals, as does transgenic attenuation of PNNs (10,11). Moreover in animals with defective memory due to pathology from mutant tau or amyloid-beta, CSPG digestion or antibody treatment to block inhibitory 4-sulphated CS-GAGs restores memory to normal levels (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel animal model was developed in which the levels of ACAN were reduced in vivo through targeted ACAN gene deletion. This attenuated the PNNs and was shown to result in reinstating of the juvenile ocular dominance plasticity, as well as providing enhancements in OR memory (Rowlands et al, ). Despite the numerous successes seen with transgenic animals in removing PNNs and enhancing plasticity, this method of modulating PNNs has both practical and moral hurdles preventing it from being a viable treatment for neurodegenerative disorders in patients at present.…”
Section: Modulation Of the Pnnsmentioning
confidence: 99%
“…This was thought to be due to the absence of two types of CSPGs (phosphacan and NCAN) in the nets (Haunsoø et al, 2000;Suttkus et al, 2014). as providing enhancements in OR memory (Rowlands et al, 2018).…”
Section: Removing Pnnsmentioning
confidence: 99%
“…in rats and investigated alterations in the ECM of the PFC where D1Rs are highly expressed [reviewed in (Beaulieu and Gainetdinov, 2011)]. In addition to BC, we also included ACAN into our investigations, since this lectican is also present at perisynaptic sites (Lendvai et al, 2013), and it is expressed in the cortex, where it was shown to act as a gatekeeper for physiological plasticity (Rowlands et al, 2018). We analyzed total BC and ACAN expression levels in the homogenate and synaptosomal fractions of the PFC.…”
Section: Increased Bc Cleavage In Synaptosomes After D1-like Da Recepmentioning
confidence: 99%